Auditory Cortical Evoked Potentials in Tinnitus Patients with Normal Audiological Presentation - Chung-Yi Lee; Fu-Shan Jaw; Shin-Liang Pan; Meng-Yi Lin; Yi-Ho Young (Journal of the Formosan Medical Association, 2007)
It is widely assumed that damage to the peripheral hearing system is an essential prerequisite for the occurrence of tinnitus. However, previous studies have failed to target tinnitus patients with normal hearing. This study aims to investigate if tinnitus patients with normal audiological presentation demonstrate increased intensity dependence at the selected frequencies. Methods: This study applied auditory cortical evoked potential test to investigate nine tinnitus patients with normal audiological presentation and nine age-and sex-matched healthy subjects without tinnitus. Auditory cortical evoked potentials (N1-P2) were elicited from stimuli at four frequencies (4000, 2000, 1000 and 500 Hz) with five intensities (50, 56, 62, 68 and 74 dB nHL). Intensity dependences by latency of N1 and amplitude of N1-P2 were surveyed at midline electrodes. Results: The results showed that the intensity dependence by latency of N1 to the pooled frequencies at three midline electrodes, e.g. Fz, Cz and Pz, revealed non-significant difference. However, significant differences existed in the intensity dependence of amplitude N1-P2 to the pooled frequencies at the Fz and Cz positions. These differences suggested that tinnitus patients tended to respond less to increased sound intensity and were inclined to weaker intensity dependence. Conclusion: Increased intensity dependence of N1-P2 component at the selected frequencies cannot be demonstrated in tinnitus patients with normal hearing. Restated, the edge frequency phenomenon fails to present in tinnitus patients with normal hearing, a different characteristic from tinnitus patients with hearing loss.